The Experimental Study on the suppression effect of Asthma and Immune response improvement of Platycodi Radix Herbal-acupuncture - Chi-Young Park; Kwon-Eui Hong (Korean Pharmacopuncture Institute, 2006)
Objectives : The aim of this study was to investigate the effect of Asthma-depression and Immunoregulation with PR-HAS(Herbal-acupuncture with Platycodi Radix infusion solution) injection at Joksamni(St36) on ovalbumin-induced asthma in mice. Methods : C57BL/6 mice were sensitized and challenged with OVA(ovalbumin) for 12 weeks(once a week). The experimental group(OVA-PR-HA) was treated with concentrations(1%) of PR-HAS at Joksamni(St36) for the later 8 weeks(3times/week). The second experimental group(OVA-Needle prick) was treated with Needle-Prick at Joksamni(St36) for the later 8 weeks(3times/week). Results : 1. The weight and total cells in the mice lung treated with PR-HA decreased significantly compared with that of control group. 2. Total leukocytes and eosinophils in BALF of the mice group treated with PR-HA decreased remarkably compared with those of control group. 3. The sticking of collagen on histological analysis of lung sections, the mice group treated with PR-HA decreased significantly compared with those of control group. 4. The concentrations of IL-4, IL-5, IgE in BALF, and IL-4, IL-5, IL-13 in serum of the mice group treated with PR-HA decreased significantly compared with those of control group. 5. The number of Gr-1+/CD11b+ and CD11b+ cells in the lungs of the mice group treated with PR-HA decreased significantly compared with that of control group. 6. The numbers of CCR3+ cells, CD4+ cells and CD8+ cells in the lungs, and CD3e+/CD69+ in the lungs of the mice group treated with PR-HA decreased significantly compared with those of control group. 7. The mRNA expression of β-actin, TNF-α, IL-4, IL-5,IL-13 in the mice group treated with PR-HA with RT-PCR decreased significantly compared with those of control group. Conclusion : These result suggests that Platycodi Radix Herbal-acupuncture at Joksamni(St36) in C57BL/6mice may be an effictive part to OVA-induced asthma in C57BL/6 mice.